Hubungan Pengetahuan Dengan Perilaku Vulva Hygiene Pada Saat Menstruasi Remaja Putri di SMPN 1 Tanete Rilau Tahun 2019 - Masita, Syarifah (Jurnal Ilmiah Amanah Akademika, 2019)
Cleanliness of the genital area, especially during menstruation is often overlooked by women. At the time of menstrual blood and sweat it out and attach to the vulva can cause genital area becomes moist. A Lack of knowledge about reproductive health would enable women do not behave hygiene during menstruation that may endanger their own reproductive health. The purpose of this study was to determine the relationship of knowledge to the behavior of vulva hygiene during menstruation in young women aged (13-15) years at SMPN 1 Tanete Rilau The method used in this research is the design of quantitative correlation models. Data collection techniques by using a questionnaire or a questionnaire, with a sample size of 80 respondents. Sampling methods using the Stratified Random Sampling. The results showed that nearly half have a good knowledge (39,75%), half of it has enough knowledge (50%), and a small portion of respondents have less knowledge (11,25%). Most behave well (85%) and a small portion of respondents behave badly (15%). From the research results in no relation between get knowledge of the behavior of vulva hygiene during menstruation in young women aged 13-15 years at SMPN 1 Tanete Rilau with result p value of 0,000. It can be concluded that there is a relationship with the behavior of vulva hygiene during menstruation in young women aged 13-15 years at SMPN 1 Tanete Rilau